Influence of the river flow pulse on the maturity, resilience, and sustainability of tropical coastal ecosystems. (January 2023) - Macedo, M.; Fabré, N.N.; da Silva, V.E.L.; Santos, M.E.F.; Albuquerque-Tenório, M.D.; Angelini, R.
Abstract: Coastal marine ecosystems have structural and functional features usually connected by the seasonal transfer of nutrients and organisms. These environments can utilize inter-ecosystem subsidies to increase resilience and maturity and support human activities like fishing. However, the importance of the connection and the role of the seasonal pulse of energy flows to enhance maturity are still poorly understood and reported. Our objective in this paper is to assess the effect of seasonal hydrological pulses on two tropical coastal interconnected ecosystems. Thus, we made four Ecopath models for estuarine and neritic environments considering the dry and rainy seasons, with a similar sampling design that allowed them to be compared. Our results provide evidence for the occurrence of the pulsed ecosystems since both environments seem driven by the river flow. Estuary presents more and more substantial differences (measured by ecosystem attributes) in both seasons because it is directly affected by river floods than the neritic environment. The neritic is affected indirectly by the movement of species from the estuary and by a weaker river flow. In the dry season, the differences between ecosystems are lower because the dry season trend to homogenize cycling, maturity, homeostasis, and resilience. We found that the seasonal river flow (pulse) forces the variability of biomass, flows, and ecosystem features, and this variance creates the required stability for both ecosystems. Still, these environments benefit through the exchange of components that relieve the pressures of predation on specific groups and maintain the energy flow necessary for the functioning of their trophic webs. The pulse by the rainfall favors connectivity and equalizes the two systems, increasing the connectivity between them and the exchange of subsidies that strengthens the trophic structures, contributing to the increase in maturity. In these ecosystems, seasonal changes become a key factor for exchanging flows that will promote sustainability, the accumulation of more biomass (growth), and the optimization of reserve energy (development) in both systems. This efficient joint strategy of perpetuation is what promotes resistance and resilience to these ecosystems, which together can reach different states of equilibrium, translated into maturity to withstand new environmental changes. Highlights: Rainfall drives the biomass exchange between estuarine and marine groups in the two ecosystems. In the rainy season, species movement increases the trophic complexity, increasing resilience and growing maturity. In the dry season, estuarine and neritic ecosystems are similar regarding biomass distribution at trophic levels. Species migration between ecosystems allows organic matter and energy transfer, confirming the ecosystem pulse theory.